Overexpression of Toll-like Receptor 4-linked Mitogen-activated Protein Kinase Signaling Contributes to Internalization of Escherichia coli in Sheep - Wang, Sutian (Int J Biol Sci, 2018)
Escherichia coli is one of the most common causal pathogens of mastitis in milk-producing mammals. Toll-like receptor 4 (TLR4) is important for host recognition of this bacteria. Increased activation of TLR4 can markedly enhance the internalization of E. coli. In this study, the relationship between TLR4 and mitogen-activated protein kinase (MAPK) signaling pathways in mediating E. coli internalization was evaluated in sheep monocytes. Using a TLR4-overexpressing transgenic (Tg) sheep model, we explored the bacterial internalization mechanism in sheep. We found that monocytes of Tg sheep could phagocytize more bacteria and exhibited higher adhesive capacity. The specific inhibition of p38 MAPK or c-Jun N-terminal kinase (JNK) or extracellular signal-regulated kinases (ERKs) reduced TLR4-dependent internalization of bacteria into sheep monocytes. Furthermore, the inhibition of MAPK signaling down-regulated the adhesive capacity of monocytes and the expression of scavenger receptors and adhesion molecules. Taken together, the overexpression of TLR4 in transgenic sheep enhanced the internalization of E. coli via MAPK signaling.